2019
DOI: 10.1371/journal.pone.0222711
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the impedance of cochlear implant devices within 24 hours of their implantation

Abstract: Cochlear implantation is a surgical procedure, which is performed on severely hearing-impaired patients. Impedance field telemetry is commonly used to determine the integrity of the cochlear implant device during and after surgery. At the Department of Otolaryngology, Cheng Hsin General Hospital (Taipei, Taiwan), the cochlear implant devices are switched on within 24 hours of their implantation. In the present study, the impedance changes of Advanced Bionics™ cochlear implant devices were compared with previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 14 publications
(17 reference statements)
1
20
1
Order By: Relevance
“…The difference is not significant between the impedance measured within 24 hours after the implantation and that measured intra-operatively in the present study (Tables 1 and 2 ). This was different to one study of the same system by the authors [ 10 ]. Our previous study was focused on patients who received HiFocus TM 1-J electrode array implantations and the patients in the present study received HiFocus TM Mid-Scala implants.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…The difference is not significant between the impedance measured within 24 hours after the implantation and that measured intra-operatively in the present study (Tables 1 and 2 ). This was different to one study of the same system by the authors [ 10 ]. Our previous study was focused on patients who received HiFocus TM 1-J electrode array implantations and the patients in the present study received HiFocus TM Mid-Scala implants.…”
Section: Discussioncontrasting
confidence: 82%
“…The above two reasons could explain the stable impedance on day one. One might wonder that a 1-J array will have more space to develop fibrosis and sheath formation [ 11 , 12 ], which in turn could lead to the sheath formation effect [ 6 , 13 ] and thus a significant increase in impedance as observed in our previous study [ 10 ]. However, a complete sheath can’t be expected to form at day one despite cell cover begins within hours of implantation [ 5 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For such applications, it should be considered that cochlear implantation causes foreign body reaction, with increased number of macrophages and fibrous tissue build-up surrounding the electrode [42]. This affects the temporal progression of electrode impedances [43]. High impedance values can also be caused by air bubbles on the electrode contact, which generally dissipate within hours to days after the surgery [8], [10].…”
Section: F Study Limitationsmentioning
confidence: 99%
“…Since the e cacy and safety of early switch-on within 24 h of surgery has previously been con rmed 17 , many CI centers, including ours, have changed the switch-on protocol over the past few years from the initial tting at 3-6 weeks post-surgery to the day after surgery. Previous studies investigating the evolution of electrode impedance after early switch-on have shown inconsistent results according to the type of electrode array [18][19][20] . To the best of our knowledge, this is the rst study to describe changes in the impedance of slim modiolar electrodes over time in CI recipients who were rehabilitated with the conventional and early switch-on protocols.…”
Section: Introductionmentioning
confidence: 98%